A survey of case studies on the use of forensic three-dimensional printing in England and Wales - Errickson, David; Carew, R. M.; Collings, A. J.; Biggs, M. J. P.; Haig, P.; O’Hora, H.; Marsh, N.; Roberts, J. (Springer, 2022)
3D printing has rapidly developed and been applied in forensic science due to its use in creating demonstrations for courts of law. Much of the literature on this specific topic has focused on the use of 3D printed models in academia, the potential influence on a jury, and its use as a long-term documentation process, but with few actual forensic case examples. This paper offers an insight into the development of 3D printing in forensic practice and how 3D printing is currently being used in the criminal justice system in England and Wales. A series of case reports were gathered from multiple police forces and forensic practitioners in the UK to identify how 3D printing was being used. These discussions established who was requesting 3D printed exhibits, what type of technologies were being utilised, what type of exhibits were being printed, and resulting feedback for the use of 3D printed material within a criminal case. As a result, this research demonstrates the current use of 3D printing in England and Wales, discussing the associated cases that have been known to incorporate 3D prints. Likewise, this work explores the limitations that have been encountered by forensic practitioners and identifies a series of research questions that should be considered in future investigations.
Keywords: Forensic science; 3D Imaging; Blunt force trauma; Dismemberment; Visual evidence; Human remains